2004
DOI: 10.2478/bf02482722
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation processes for decolorization of aqueous solution containing acid red G azo dye

Abstract: Some investigations concerning the decolorization of Acid Red G azo dye by photooxidation with hydrogen peroxide were performed. The influences of pH, oxidant concentration, and the presence of Fe 2+ or other metal ions (Co 2+ , Cu 2+ , Ni 2+ , Mn 2+ ) as potential catalysts, were investigated. The best results were obtained in the presence of ferrous ions in acid and neutral media. The other ions are not as effective as Fe 2+ for dye decolorization. Co 2+ and Cu 2+ ions have a catalytic action, at low concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…[15] The presence of phosphonate on the HNTs surface was thus assessed by XPS spectra, where a signal at 133.9 eV, ascribed to phosphorus [20] is well evident after functionalization with AEPA (Figure S1, Supporting Information). Moreover, since 31 P chemical shifts are sensitive to changes of OPO bond angle and to the electronegativity of the proximal atoms, the solid-state NMR (SS-NMR) was used for investigating the interaction between the phosphonic acid headgroup and the oxide surface. [21] As shown in Figure S2, Supporting Information, the 31 P CP (cross-polarization) SS-NMR spectrum of HNTs-AEPA displays a significant change with respect to the one of AEPA, with a meaningful upfield shift of the signals (from 19.4 to 6-14 ppm).…”
Section: Preparation Of Hnts-aepa/ru 4 Pommentioning
confidence: 99%
“…[15] The presence of phosphonate on the HNTs surface was thus assessed by XPS spectra, where a signal at 133.9 eV, ascribed to phosphorus [20] is well evident after functionalization with AEPA (Figure S1, Supporting Information). Moreover, since 31 P chemical shifts are sensitive to changes of OPO bond angle and to the electronegativity of the proximal atoms, the solid-state NMR (SS-NMR) was used for investigating the interaction between the phosphonic acid headgroup and the oxide surface. [21] As shown in Figure S2, Supporting Information, the 31 P CP (cross-polarization) SS-NMR spectrum of HNTs-AEPA displays a significant change with respect to the one of AEPA, with a meaningful upfield shift of the signals (from 19.4 to 6-14 ppm).…”
Section: Preparation Of Hnts-aepa/ru 4 Pommentioning
confidence: 99%
“…Fenton's reagent (a mixture of H 2 O 2 and Fe 2þ /Fe 3þ ) is one of the most common homogeneous catalytic systems for decomposition of synthetic dyes (Meric et al, 2004;Sun et al, 2007;Ramirez et al, 2005;Karci, 2014). Copper, cobalt, chromium, aluminum, nickel, manganese, and other soluble salts also demonstrated higher catalytic activities (Bokare and Choi, 2014;Surpateanu and Zaharia, 2004;Xu et al, 2004;Ling et al, 2010;Zhan et al, 2011). However, the recovery of homogeneous catalysts from the effluents is difficult and requires additional separation steps which increase the cost for wastewater treatment.…”
Section: Introductionmentioning
confidence: 95%
“…The selection of Mn 2+ , Cu 2+ , Co 2+ , and Ni 2+ as dopants was mainly because they have versatile redox chemistry which might be able to significantly improve the catalytic activity of titania. 3032 For comparison purpose, the flower-like titania nanospheres without metal ion doping were also fabricated. It was confirmed that the presence of transition-metal ion dopants (especially Mn 2+ ) was indeed highly useful to improve the catalytic activity of titania.…”
Section: Introductionmentioning
confidence: 99%